A Structural-Methodological Model for Parallel Teaching of Two Foreign Languages in Kazakhstani Universities (Eurasian Journal of Philology Science and Education, 2026)
Parallel foreign language teaching in Kazakhstani universities requires not only the simultaneous inclusion of two foreign languages in the curriculum, but also their methodological coordination as interrelated components of one educational process. In teacher-training programmes such as “Foreign Language: Two Foreign Languages”, English is usually studied as the first foreign language, while French, German, Chinese or another language is introduced as the second foreign language. In actual practice, however, the two languages are often taught as separate subjects, with different syllabi, unequal academic hours and insufficient coordination between teachers. This creates a methodological contradiction between the expected development of communicative competence in two foreign languages and the lack of mechanisms for cross-linguistic transfer, contrastive analysis and interference management.The purpose of this article is to substantiate the methodological foundations of parallel foreign language teaching and to propose a structural-methodological model for coordinating English as the first foreign language and French as the second foreign language. The study is based on competence-based, communicative-cognitive, contrastive, integrative and metalinguistic approaches. The research methods include analysis of educational programmes and syllabi, diagnostic survey, oral questioning and theoretical modelling. The empirical part involved 83 respondents: 76 students and graduates and 7 teachers connected with the English-French language combination in the 2024-2025 academic year.The findings indicate that the main difficulty is the absence of a coordinated methodological system. The article identifies key conditions for parallel teaching: topic synchronization, contrastive grammar and vocabulary tasks, metalinguistic awareness, transfer and interference management, teacher coordination and CEFR-based assessment. The proposed model includes target, content, organizational-methodological, processual and assessment-diagnostic components. Its practical value lies in its application to curriculum design, syllabus development and classroom practice.Keywords: parallel foreign language teaching, methodological coordination, cross-linguistic transfer, metalinguistic awareness.